1990
DOI: 10.1007/bf00328165
|View full text |Cite
|
Sign up to set email alerts
|

Flight morphology of Neotropical butterflies: palatability and distribution of mass to the thorax and abdomen

Abstract: We test whether palatability of Neotropical butterflies is associated with distribution of mass to the thorax and abdomen. Thoracic mass is predominantly muscle mass, whereas abdominal mass includes organs of digestion, food storage, and reproduction. To escape from predation, butterflies palatable to the rufous-tailed jacamar (Galbula ruficauda) use fast, erratic flight, whereas unpalatable butterflies have defensive chemicals and slow, regular flight patterns. We adjusted for effects of phylogeny and report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 15 publications
2
108
0
1
Order By: Relevance
“…Since several studies indicate that relative thorax mass correlates with flight performance (e.g. Srygley & Chai 1990 ;Wickman 1992), flight performance and flight manoeuvrability might actually increase with reduced body size.…”
Section: Discussionmentioning
confidence: 99%
“…Since several studies indicate that relative thorax mass correlates with flight performance (e.g. Srygley & Chai 1990 ;Wickman 1992), flight performance and flight manoeuvrability might actually increase with reduced body size.…”
Section: Discussionmentioning
confidence: 99%
“…These rearing environments predictably affected the flight morphology of the adult butterflies. Individuals that developed in the low-quality site had higher wing loadings, a trait positively associated with flight speed and perfor mance (Dudley 1990;Srygley and Chai 1990), than in dividuals that developed in the high-quality site. Thorax mass and wing loading strongly affect flight capacity in Lepidoptera (Srygley and Chai 1990).…”
Section: Dispersal Capacitymentioning
confidence: 99%
“…Individuals that developed in the low-quality site had higher wing loadings, a trait positively associated with flight speed and perfor mance (Dudley 1990;Srygley and Chai 1990), than in dividuals that developed in the high-quality site. Thorax mass and wing loading strongly affect flight capacity in Lepidoptera (Srygley and Chai 1990). In a study of mul tiple species of Neotropical Lepidoptera, Srygley and Chai (1990) found that populations located in pasture habitats dispersed more and differed in wing and thorax allocation patterns, corrected for body size.…”
Section: Dispersal Capacitymentioning
confidence: 99%
See 2 more Smart Citations